Penyuluhan Hukum Mengenai Larangan Pencantuman Klausula Baku Bagi Pelaku Usaha dalam Rangka Mewujudkan Pelindungan Konsumen - Agus Suwandono; Deviana Yuanitasari; Nun Harrieti; Etty Mulyati; Holyness N. Singadimedja; Rafan Darodjat (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Standard clauses in consumer protection are terms or conditions unilaterally determined by business actors. Standard clauses are regulated in Article 18 of the Consumer Protection Act. Understanding standard clauses is essential for consumers and business actors, so legal counseling is needed to increase awareness and understanding for consumers and business actors. The Consumer Protection Act does not prohibit the inclusion of standard clauses in agreement documents between consumers and business actors. The Consumer Protection Act only prohibits the inclusion of standard clauses contrary to Article 18, paragraphs (1) (2) of the Consumer Protection Act. Article 18 paragraph (3) of the Consumer Protection Act determines that the standard clause that contradicts Article 18 paragraph (1), (2) of the Consumer Protection Act is declared null and void. In addition, the legal consequences for business actors for the inclusion of standard clauses that are contrary to Article 18 paragraph (1), (2) of the Consumer Protection Act based on Article 62 paragraph (1) of the Consumer Protection Act are threatened with imprisonment for a maximum of five years or a maximum fine of two billion. In including standard clauses in documents or agreements with consumers, business actors must pay attention to the provisions of Article 18 of the Consumer Protection Act. This legal counseling activity increases the awareness and understanding of consumers and business actors regarding standard clauses based on consumer protection laws, which can ultimately realize consumer protection.